SEXUAL BEHAVIOR, KNOWLEDGE LEVEL, AND CONDOM USE AMONG MSM AND TRANSGENDER COMMUNITIES IN BAUBAU CITY : SEXUAL BEHAVIOR, KNOWLEDGE LEVEL, AND CONDOM USE - Justin, Wa Ode Sitti; Anita, Anita; P, Sudirman; Ruslan, Winda Angraeni; J, Ahmad Amiruddin (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: The MSM (Men who have Sex with Men) and transgender communities are key populations at high risk for sexually transmitted infections (STIs), including HIV/AIDS. This vulnerability is driven by risky sexual behaviors, low consistency in condom use, as well as stigma and discrimination that hinder access to community-friendly healthcare services. Empirical data on these issues in Baubau City remain limited, making this study essential to provide a comprehensive overview. Methods: This study employed a quantitative descriptive survey method with a cross-sectional approach. The sample consisted of 60 respondents, including 54 MSM and 6 transgender individuals, selected through purposive and snowball sampling techniques. Data were collected using a structured questionnaire measuring knowledge of HIV and STIs, risky sexual behaviors, and condom use. Descriptive statistics were used for data analysis. Results: The majority of respondents engaged in risky sexual behaviors, with 63% having more than one partner in the past six months, 92% having practiced anal sex, and 55% having engaged in transactional sex. Although 66.7% of respondents demonstrated a high level of knowledge about HIV and STIs, there remains a significant gap between knowledge and safe sexual practices. Consistent condom use during anal sex was reported by only 30% of respondents, and the use of water-based lubricants was similarly low. Conclusion: Risky sexual behavior remains prevalent among MSM and transgender communities in Baubau City despite relatively high knowledge levels. Condom and lubricant use is still inconsistent. Comprehensive education interventions, improved access to condoms and lubricants, and strengthened community-friendly healthcare services are necessary to promote safer sexual behaviors.